2020
DOI: 10.3390/ijerph17165728
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception and Depression in Public Health Crises: Evidence from the COVID-19 Crisis in China

Abstract: Background: Scant attention has been paid to how risk perceptions of public health crises may affect people’s mental health. Aims: The aims of this study are to (1) construct a conceptual framework for risk perception and depression of people in public health crises, (2) examine how the mental health of people in the crisis of Coronavirus Disease 2019 (COVID-19) is affected by risk perception and its associated factors, including distance perception of the crisis and support of prevention and control policies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(138 citation statements)
references
References 47 publications
8
116
0
1
Order By: Relevance
“…This study found that 29.7% of participants reported moderate to severe depressive symptoms and this result was similar to studies conducted in China and Italy, which found that 25% and 32.8% of the participants, respectively had moderate to severe depressive symptoms during the COVID-19 pandemic [27,28]. The level of depressive symptoms can be affected by the risk perception of health crisis.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This study found that 29.7% of participants reported moderate to severe depressive symptoms and this result was similar to studies conducted in China and Italy, which found that 25% and 32.8% of the participants, respectively had moderate to severe depressive symptoms during the COVID-19 pandemic [27,28]. The level of depressive symptoms can be affected by the risk perception of health crisis.…”
Section: Discussionsupporting
confidence: 86%
“…Personal knowledge, trust in government, healthcare professionals and science, and information of COVID-19 collected from friends and family are significant predictors of risk perception [30]. Additionally, affective risk perception, which is strongly subjective, is positively associated with the depressive symptoms during the COVID-19 pandemic, while negative association is found between cognitive risk perception, meaning individual judgement is based on scientific support, and depressive symptoms [27]. Risk perception may result in changes in daily routines such as paying more attention to personal hygiene and browsing more prevention information during the pandemic, hence, affecting depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting future direction would be to examine how university students' health risk perceptions impact their academic emotions and engagement. Both the antecedents and the consequences (Ding et al, 2020) of health risk perceptions during COVID-19 have been examined by recent research. For example, examined the relationship between COVID-19 health risk perceptions and emotions among quarantined adolescents in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Although a lockdown increases the chance of effectively dealing with COVID-19, it also contributes to a decrease in people's well-being [1][2][3][4], invoking several adverse emotional reactions such as anger, fear, confusion, irritability, frustration, elevated stress, insomnia, and nervousness [1,4,5]. Thousands of people have lost their work and socio-economic status during the COVID-19 pandemic.…”
Section: Mental Health During the Covid-19 Pandemicmentioning
confidence: 99%